Insulin‐responsive autonomic neurons in rat medulla oblongata. Issue 16 (18th October 2018) - Senthilkumaran, M.; Bobrovskaya, L.; Verberne, A. J. M.; Llewellyn‐Smith, I. J.
Abstract: Low blood glucose activates brainstem adrenergic and cholinergic neurons, driving adrenaline secretion from the adrenal medulla and glucagon release from the pancreas. Despite their roles in maintaining glucose homeostasis, the distributions of insulin‐responsive adrenergic and cholinergic neurons in the medulla are unknown. We fasted rats overnight and gave them insulin (10 U/kg i.p.) or saline after 2 weeks of handling. Blood samples were collected before injection and before perfusion at 90 min. We immunoperoxidase‐stained transverse sections of perfused medulla to show Fos plus either phenylethanolamine N ‐methyltransferase (PNMT) or choline acetyltransferase (ChAT). Insulin injection lowered blood glucose from 4.9 ± 0.3 mmol/L to 1.7 ± 0.2 mmol/L (mean ± SEM ; n = 6); saline injection had no effect. In insulin‐treated rats, many PNMT‐immunoreactive C1 neurons had Fos‐immunoreactive nuclei, with the proportion of activated neurons being highest in the caudal part of the C1 column. In the rostral ventrolateral medulla, 33.3% ± 1.4% ( n = 8) of C1 neurons were Fos‐positive. Insulin also induced Fos in 47.2% ± 2.0% ( n = 5) of dorsal medullary C3 neurons and in some C2 neurons. In the dorsal motor nucleus of the vagus (DMV), insulin evoked Fos in many ChAT‐positive neurons. Activated neurons were concentrated in the medial and middle regions of the DMV beneath and just rostral to the area postrema. In control rats, very few C1, C2, or C3 neurons and no DMV neurons were Fos‐positive. The high numbers of PNMT‐immunoreactive and ChAT‐immunoreactive neurons that express Fos after insulin treatment reinforce the importance of these neurons in the central response to a decrease in glucose bioavailability. Abstract : Insulin activates adrenergic and cholinergic neurons in rat medulla. Of adrenergic neurons, more than half of caudal C1 neurons, one‐third of rostral C1 neurons, and half of adrenergic C3 neurons are Fos‐immunoreactive after insulin treatment. Insulin also evokes Fos expression in many dorsal vagal motor neurons.